The Role of Electoral Incentives for Policy Innovation: Evidence from the U.S. Welfare Reform - Andreas Bernecker; Pierre C. Boyer; Christina Gathmann (Center for Economic Studies and ifo Institute (CESifo), 2018)
We investigate whether the decision to experiment with novel policies is influenced by electoral incentives. Our empirical setting is the U.S. welfare reform in 1996, which marked the most dramatic shift in social policy since the New Deal. We find that electoral incentives matter: governors with strong electoral support are less likely to experiment with policies than governors with little electoral support. Yet, governors who cannot be reelected experiment more than governors striving for reelection. The importance of electoral incentives is robust to controlling for governor ideology, voter preferences for redistribution, the influence of the legislature, or for learning among states. A comparison of the role of governor ideology and electoral incentives reveals that both contribute about equally to policy experimentation.
Keywords: D72; D78; H75; 330; policy innovation; electoral incentives; welfare reform; spillovers